Integrated model for estimation of the interaction between surface water and groundwater based on in valley watershed - Yun YANG; Yong GUO; Fafei WANG; Jian SONG; Jianfeng WU (Shuiwen dizhi gongcheng dizhi)
Previous studies on surface water-groundwater (SW-GW) interactions have primarily focused on plain river networks, with limited understanding on hydrodynamic interactions in valley-type watersheds. This study focuses on the Beishan Reservoir Basin (BRB) in Jurong, specifically investigating surface runoff and shallow groundwater interactions in a valley-type watershed Jurong. A coupled SWAT-MODFLOW model was developed to evaluate the spatiotemporal variations in SW-GW interaction processes. The results show that the interaction between SW-GW varies both temporally and spatially. Temporally, the groundwater discharged into the surface water during 2016−2019, while the surface water replenished the groundwater during certain periods of wet season. Spatially, the mountainous areas in the northwest and northeast of the study area and the surrounding areas of BRB in the south of the study area are characterized by groundwater discharge into surface water. The coupling model effectively describes the surface water-groundwater (SW-GW) interaction, with groundwater contributing 8.72% to the net replenishment of rivers in the basin. The western tributaries and central tributaries of the basin receive 28.8% and 79.8% groundwater recharge in the whole basin, respectively. The eastern tributaries with negative groundwater recharge rate of 8.6% exhibit surface water discharge into groundwater. This study provides a technical support for joint scheduling and development and utilization of watershed water resources.